Neuroprotection unveiled: melatonin mitigates apoptotic pathways in traumatic brain injury - Gunara, Sezer Onur; Akgun, Mehmet Yigit; Seker, Ugur; Ucar, Ege Anil; Ates, Ozkan; Basar, Ibrahim (Frontiers in Neurology, 2025)
ObjectiveThis study investigated the neuroprotective effects of melatonin in mice subjected to traumatic brain injury (TBI), focusing on caspase-dependent apoptotic signaling pathways.Materials and methodsA total of 21 mice were divided into three groups: control, trauma (TBI), and trauma + melatonin (TBI + M). TBI was induced in the TBI and TBI + M groups via a free-fall impact on the frontal lobes. A single dose of 10 mg/kg of melatonin was intraperitoneally administered to the TBI + M group. Brain tissues were collected for histological evaluation and immunohistochemical analysis of apoptotic proteins.ResultsThe control group showed normal brain morphology, while the trauma group exhibited significant tissue loss and demyelination. The TBI + M group demonstrated reduced demyelination compared to the trauma group. An immunohistochemical analysis revealed increased expression of Bax and decreased expression of Bcl-2 in the trauma group, both of which were mitigated by melatonin treatment. The expression levels of caspase-3 and caspase-9 were elevated in the trauma group, whereas the TBI + M group showed expression levels comparable to the control group.ConclusionTBI increased apoptotic protein expression, indicating neurodegeneration. The administration of melatonin at 10 mg/kg attenuated TBI-induced apoptosis and demyelination while promoting anti-apoptotic protein expression in the experimental model. These findings suggest a potential therapeutic role for melatonin in the management of TBI.